AI Meets Marketing: Unearthing Next-Gen Campaign Strategies with AI-Powered Tool - Asep Koswara (Marketing and Business Strategy, 2025)
This study explores AI's capabilities for generating innovative digital marketing strategies through a practical analysis using AskOptimo, an AI-powered marketing tool. Using a descriptive research methodology, this study aims to evaluate the types of campaign strategies developed by AskOptimo, assess their strategic value, and determine their alignment with industry best practices, particularly in the wedding industry. By analyzing the generated ideas, the study identifies the strengths and limitations of AI in digital marketing and offers insights into its potential to streamline the campaign ideation process. The results reveal that AskOptimo offers efficient, diverse marketing suggestions; the ideas often reflect common industry approaches but lack the emotional and contextual depth needed for the wedding sector. The study also highlights the need for a hybrid approach that combines AI with human creativity to develop innovative and impactful marketing campaigns. The findings provide insights for businesses, marketers, and researchers interested in AI's role in shaping modern marketing strategies. Managerially, the study suggests that companies should not rely solely on AI tools but instead use them as support systems to enhance, rather than replace, human-led strategic thinking particularly in emotionally nuanced industries like weddings.